Course of fear of falling after hip fracture: findings from a 12-month inception cohort - Wilco P Achterberg; Miriam L Haaksma; Maaike N Scheffers-Barnhoorn; Arthur HP Niggebrugge; Max PL van der Sijp; Jolanda CM van Haastregt; Monica van Eijk (BMJ Open, 2023)
Objectives To examine the course of fear of falling (FoF) up to 1 year after hip fracture, including the effect of prefracture FoF on the course.Design Observational cohort study with assessment of FoF at 6, 12 and 52 weeks after hip fracture.Setting Haaglanden Medical Centre, the Netherlands.Participants 444 community-dwelling adults aged 70 years and older, admitted to hospital with a hip fracture.Main outcome measure Short Falls Efficacy Scale International (FES-I), with a cut-off score ≥11 to define elevated FoF levels.Results Six weeks after hip fracture the study population-based mean FES-I was located around the cut-off value of 11, and levels decreased only marginally over time. One year after fracture almost one-third of the population had FoF (FES-I ≥11). Although the group with prefracture FoF (42.6%) had slightly elevated FES-I levels during the entire follow-up, the effect was not statistically significant. Patients with persistent FoF at 6 and 12 weeks after fracture (26.8%) had the highest FES-I levels, with a mean well above the cut-off value during the entire follow-up. For the majority of patients in this group, FoF is still present 1 year after fracture (84.9%).Conclusions In this study population, representing patients in relative good health condition that are able to attend the outpatient follow-up at 6 and 12 weeks, FoF as defined by an FES-I score ≥11 was common within the first year after hip fracture. Patients with persistent FoF at 12 weeks have the highest FES-I levels in the first year after fracture, and for most of these patients the FoF remains. For timely identification of patients who may benefit from intervention, we recommend structural assessment of FoF in the first 12 weeks after fracture.